DETERMINATION, ISOLATION, AND IDENTIFICATION OF AUCUBIN AND VERBASCOSIDE IN THE LEAVES OF IRAQI PLANTAGO LANCOLETA L. USING DIFFERENT DETECTING METHODS - Khalaf, Hasan A.; Abbas, Ibrahim S.; Tawfeeq, Amani A.; Mahdi, Monther F. (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: Plantago lanceoleta L. (ribwort plantain) is one of the important medicinal herbs which is widespread fortune available in Iraq, that have a wide range of medicinal properties. The aim of this work was to determine, isolate and identify verbascoside and aucubin in Iraqi P. lanceoleta L. by using different chromatographic and spectrometric methods. Methods: Verbascoside and aucubin were isolated and quantified by preparative TLC, and then they were determined by the high-performance thin-layer chromatography (HPTLC) fingerprinting. Aucubin and catalpol in the plant extract were analyzed by liquid chromatography-mass spectrometry (LC-MS); aucubin and verbascoside that isolated from the plant sample were examined by fourier-transform infrared spectroscopy (FT-IR) and LC-MS, respectively. Results: The result showed that the Iraqi P. lanceoleta L. contains 1.74 percent (verbascoside) and 0.24 percent (aucubin) of dry powdered leaves. Each TLC-isolated compound showed a single spot on the HPTLC plate, which give an idea about the purity of the isolated compound. Aucubin (with catalpol) and verbascoside both are detected by LC-MS in different ionization mode. Many functional groups were identified in the TLC-isolated aucubin by FT-IR. Conclusion: The Iraqi P. lanceoleta L. showed a high content of verbasoside, and it is a very rich source for this compound, which can be easily isolated by TLC and subjected to many pharmacological studies. The extract of the young leaves of this plant gave a little amount of aucubin, and it is easy to obtain a higher content from the older leaves.